Effects of 6-months' Exercise on Cardiac Function, Structure and Metabolism in Female Hypertensive Rats–The Decisive Role of Lysyl Oxidase and Collagen III - Schreckenberg, Rolf; Horn, Anja-Maria; da Costa Rebelo, Rui M.; Simsekyilmaz, Sakine; Niemann, Bernd; Li, Ling; Rohrbach, Susanne; Schlüter, Klaus-Dieter (Frontiers in Physiology, 2017)
Purpose: According to the current therapeutic guidelines of the WHO physical activity and exercise are recommended as first-line therapy of arterial hypertension. Previous results lead to the conclusion, however, that hearts of spontaneously hypertensive rats (SHR) with established hypertension cannot compensate for the haemodynamic stresses caused by long-term exercise. The current study was initiated to investigate the effects of aerobic exercise on the cardiac remodeling as the sole therapeutic measure before and during hypertension became established. Methods: Beginning at their 6th week of life, six SHR were provided with a running wheel over a period of six months. Normotensive Wistar rats served as non-hypertensive controls. Results: In Wistar rats and SHR, voluntary exercise led to cardioprotective adaptation reactions that were reflected in increased mitochondrial respiration, reduced heart rate and improved systolic function. Exercise also had antioxidant effects and reduced the expression of maladaptive genes (TGF-β1, CTGF, FGF2). However, at the end of the 6-months’ training, the echocardiograms revealed that SHR runners developed a restrictive cardiomyopathy. The induction of lysyl oxidase (LOX), which led to an increased network of matrix proteins and a massive elevation in collagen III expression, was identified as the underlying cause. Conclusions: Running-induced adaptive mechanisms effectively counteract the classic remodeling of hearts subject to chronic pressure loads. However, with sustained running stress, signaling pathways are activated that have a negative effect on left ventricular relaxation. Our data suggest that the induction of LOX may play a causative role in the diagnosed filling disorder in trained SHR.